Oxidative Stress in Endometrial Flushing Fluid of Patients with Polycystic Ovary Syndrome, Endometrioma and Uterine Leiomyoma: Comparison with Healthy Controls - Demir, Mustafa; Ince, Onur; Yilmaz, Bulent; Barut, Mert Ulas; Ozturk, Ulviye Cansu; Kılıc, Avni; Turp, Ahmet Berkiz; Sutcu, Recep; Taysi, Seyithan (Gynecology Obstetrics & Reproductive Medicine, 2020)
OBJECTIVE: Polycystic ovary syndrome, myoma uteri and endometrioma are frequently seen gynecologic problems and all three diseases may cause infertility. Aim of this cross-sectional study was to compare total antioxidant status, ceruloplasmin, total sulfhydryl , total oxidant status, lipid hydroperoxide and oxidative stress index levels in endometrial flushing fluid of patients with Polycystic ovary syndrome (n=20), uterine leiomyoma (n=20), endometrioma (n=19), and healthy women (n=20). STUDY DESIGN: We compare endometrial flushing fluid of patients with polycystic ovary syndrome (n=20), uterine leiomyoma (n=20), endometrioma (n=19) and healthy women (n=20). Endometrial flushing fluid samples were collected during the implantation window of all women. RESULTS: Mean age of groups was 28.90±5.45, 37.25±2.73, 32.84±6.62 and 32.15±5.18 in Polycystic ovary syndrome, myoma uteri, endometrioma and control groups, respectively (p<0.05). Mean total antioxidant status, ceruloplasmin and total sulfhydryl levels indicating antioxidant state were comparable between Polycystic ovary syndrome, myoma uteri, endometrioma and control groups (p=0.806, p=0.156, p=0.328 respectively for markers). Similarly, oxidant state-related markers didn’t differ significantly between 4 groups (p=0.090 for total oxidant status, p=0.087 for lipid hydroperoxide, p=0.312 for oxidative stress index). CONCLUSION: Endometrial flushing fluid total antioxidant status, total oxidant status, lipid hydroperoxide, ceruloplasmin, and total sulfhydryl levels during implantation window didn’t differ between women with Polycystic ovary syndrome, uterine leiomyoma, endometrioma, and healthy controls.